The impact of road environments on rural periodic market travel satisfaction: a heterogeneity analysis of travel modes - Xu, Hong; Liang, Ping; Zhu, Hao; Li, Mingyang; Li, Haimei; Martek, Igor; Ao, Yibin (Frontiers in Public Health, 2024)
Introduction Travel satisfaction as experienced by rural residents is closely related to personal physical and mental health, as well as rural economic conditions. An improved rural road environment can be expected to enhance villagers’ satisfaction with regards to visits to markets, but to date this has not been established empirically. Methods In this study, a questionnaire was designed to obtain local residents’ evaluations of road environment characteristics for periodic market travel. And we use an Oprobit regression model and Importance-Performance Map Analysis (IPMA) to explore the heterogeneity of the 14 key elements of the “home-to-market” road environment impact on villagers’ satisfaction under different modes of travel. Results The results of the study reveal that villagers expressed dissatisfaction with the current lack of sidewalks and non-motorized paths, and except for road traffic disturbances and road deterioration, which did not significantly affect mode of travel, other factors proved significant. Significantly, bus services are associated with a significant positive effect on walking, non-motorized and bus travel satisfaction, while distance travel also affects walking, non-motorized and motorized travel satisfaction. It is worth noting that greening and service facilities negatively affect motorized travel satisfaction. In summary, road width, sidewalks, bus service, and road deterioration, are among the elements most in need of urgent improvement for all modes of travel. Discussion The characteristics of the road environment that influence satisfaction with travel to the periodic market vary by travel mode, and this study is hoped to provide data support and optimization recommendations for the improvement of the rural road environment in China and other countries.